Pengaruh Pajak Daaerah dan Retribusi terhadap Pendapatan Asli Daerah Kabupaten Dairi - Br Barus, Agnes Avenia; Elfrida Purba, Enjel; Lubis, Putri Kemala Dewi; I Manjo, Fitria (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the influence of regional levies and regional taxes simultaneously and partially on local original income in Dairi Regency for the period 2012-2021. The sample for this research is data on Regional Taxes, Regional Levy and data on Original Regional Income in Dairi Regency for the period of time 2012-2021. The sampling technique used is the saturated sampling method, namely determining the sample with the entire population used as the research sample. The data analysis technique used in this research is multiple linear regression. The research results show that partially regional taxes have a significant effect on Original Income Dairi Regency area, and regional levies do not have a significant influence on Dairi Regency's original regional income. Simultaneously or together, regional taxes and regional levies have an influence on Dairi Regency's Original Regional Income